Analisis Kausalitas Nilai Tukar Rupiah/USD, Dow Jones Industrial Average (DJIA), Nikkei225, Shanghai Index Composite (SSEC) Terhadap Indeks Harga Saham Gabungan (IHSG) - Adira Prameswari Puteri; Nora Amelda Rizal (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The COVID-19 pandemic has had a negative effect on global stock markets. In addition, the increase in the number of confirmed cases of COVID-19 further increased the volatility of the exchange rate. This study aims to determine whether there is a causal relationship between the Exchange Rate, the Dow Jones Industrial Average (DJIA), the Nikkei225 Index, and the Shanghai Stock Exchange Composite Index (SSEC) and the Composite Stock Price Index (CSPI). The research method used is the Augmented Dickey Fuller Unit Root Test, and Granger Causality. The results of the study using Granger Causality indicate that the Exchange Rate, DJIA Index, and Nikkei225 Index have a causal relationship to the Composite Stock Price Index. The SSEC index does not have a causal relationship with the Composite Stock Price Index. This means that the JCI movement has the influence of the Exchange Rate, the DJIA Index, and the Nikkei225 Index.